Single-Cell Transcriptomic Map of the Human and Mouse Bladders - Yu, Zhenyuan; Liao, Jinling; Chen, Yang; Zou, Chunlin; Zhang, Haiying; Cheng, Jiwen; Liu, Deyun; Li, Tianyu; Zhang, Qingyun; Li, Jiaping; Yang, Xiaobo; Ye, Yu; et al. (Journal of the American Society of Nephrology, 2019)
Having a comprehensive map of the cellular anatomy of the normal human bladder is vital to understanding the cellular origins of benign bladder disease and bladder cancer. We used single-cell RNA sequencing (scRNA-seq) of 12,423 cells from healthy human bladder tissue samples taken from patients with bladder cancer and 12,884 cells from mouse bladders to classify bladder cell types and their underlying functions. We created a single-cell transcriptomic map of human and mouse bladders, including 16 clusters of human bladder cells and 15 clusters of mouse bladder cells. The homology and heterogeneity of human and mouse bladder cell types were compared and both conservative and heterogeneous aspects of human and mouse bladder evolution were identified. We also discovered two novel types of human bladder cells. One type is and interstitial cells which may be associated with nerve conduction and allergic reactions. The other type is epithelial cells that may be involved with bladder emptying. We verify these epithelial cells also occur in rat and mouse bladders. This transcriptomic map provides a resource for studying bladder cell types, specific cell markers, signaling receptors, and genes that will help us to learn more about the relationship between bladder cell types and diseases.